Actuator fault detection and isolation on a quadrotor unmanned aerial vehicle modeled as a linear parameter-varying system - Julio Alberto Guzmán-Rabasa; Francisco Ronay López-Estrada; Brian Manuel González-Contreras; Guillermo Valencia-Palomo; Mohammed Chadli; Madain Pérez-Patricio (Measurement + Control, 2019)
This paper presents the design of a fault detection and diagnosis system for a quadrotor unmanned aerial vehicle under partial or total actuator fault. In order to control the quadrotor, the dynamic system is divided in two subsystems driven by the translational and the rotational dynamics, where the rotational subsystem is based on a linear parameter-varying model. A robust linear parameter-varying observer applied to the rotational subsystem is considered to detect actuator faults, which can occur as total failures (loss of a propeller or a motor) or partial faults (degradation). Furthermore, fault diagnosis is done by analyzing the displacements of the roll and pitch angles. Numerical experiments are carried out in order to illustrate the effectiveness of the proposed methodology.